UJI EFEKTIVITAS ANTIKOLESTEROL KOMBINASI EKSTRAK ETANOL DAUN AFRIKA (Gymnanthemum amygdalina Del.) DENGAN EKSTRAK ETANOL DAUN KELAPA SAWIT (Elaeis guineensis Jacq.) PADA TIKUS HIPERKOLESTEROL - Herviani Sari; Nurmaulia Nurmaulia; Wahyudi Wahyudi; Firdaus Fahdi (Fakultas Farmasi Institut Kesehatan DELI HUSADA Deli Tua, 2020)
African leaves (Gymnanthemum amygdalina Del.) and palm leaves (Elaeis guineensis Jacq.) which is contain flavonoid, saponin, alkaloid, and tannin can be used to decrease cholesterol levels and reduced the risk of cardiovascular disease. This study aims to determine the effect of EEDA dan EEDKS combination on blood cholesterol levels in hypercholesterolemic mice. Sample in this study was African leaves and palm leaves which were taken purposively without comparing samples from other regions, then extracted by maceration using ethanol 96%. The results of data analysis from the three EEDA and EEDKS groups effected cholesterol reduction due to the sig value <0.05. Based on ANOVA one way analysis of the five most effective treatments is simvastatin then dose 400-600mg/kgBB, dose 200-300mg/kgBB, dose 100-150mg/kgBB and CMC Na 1%. The combination of EEDA and EEDKS has an antihypercholesterol effect, the combination of EEDA and EEDKS has an antihypercholesterol effect that is comparable to the positive control, and the finding from this study that the most effective dosage of EEDA and EEDKS as antihypercholesterol is at dosage 400-600 mg/kgBB.